2015
DOI: 10.1002/jcph.472
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the persistence of anacetrapib and evacetrapib concentrations using two pharmacokinetic modeling approaches

Abstract: Anacetrapib, a cholesterol ester transfer protein (CETP) inhibitor, has been reported to have longer elimination half-life after longer treatment. Two pharmacokinetic model-based approaches were used to assess whether evacetrapib, another CETP inhibitor, could behave similarly. Using population pharmacokinetic (PopPK) modeling, evacetrapib and anacetrapib pharmacokinetics were characterized using available concentration-time data, and steady-state conditions were simulated. Published 2-compartment models for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Anacetrapib showed a long t ½ in clinical studies, and in some patients, detectable plasma concentrations were observed up to 4 years after the end of treatment [ 21 ]. Population pharmacokinetic modeling of anacetrapib indicated a deep tissue compartment consistent with accumulation in adipose tissue, which was confirmed with human tissue biopsy [ 22 , 23 ]. Preliminary modeling of dalcetrapib concentrations obtained in nine clinical studies ranging from phase I to phase III (8466 samples from 2861 subjects) showed that a two-compartment model provided a good fit to the data, and the fit was not improved by adding a third compartment to simulate an adipose tissue depot (unpublished data).…”
Section: Pharmacokineticsmentioning
confidence: 80%
“…Anacetrapib showed a long t ½ in clinical studies, and in some patients, detectable plasma concentrations were observed up to 4 years after the end of treatment [ 21 ]. Population pharmacokinetic modeling of anacetrapib indicated a deep tissue compartment consistent with accumulation in adipose tissue, which was confirmed with human tissue biopsy [ 22 , 23 ]. Preliminary modeling of dalcetrapib concentrations obtained in nine clinical studies ranging from phase I to phase III (8466 samples from 2861 subjects) showed that a two-compartment model provided a good fit to the data, and the fit was not improved by adding a third compartment to simulate an adipose tissue depot (unpublished data).…”
Section: Pharmacokineticsmentioning
confidence: 80%
“…We previously found that hCETPtg mice have approximately 22% higher cholesterol content in their brains compared to wild type mouse brains 35 . The elevated cholesterol content in the brain and in the periphery of hCETPtg mice could differentially affect the distribution and elimination kinetics of the very lipophilic CETP inhibitors (evacetrapib has an octanol to water partition coefficient of logP 7.56) 41 . Due to these fundamental physiological differences, pharmacokinetic parameters of a CETP inhibitor should be assessed in hCETPtg mice rather than wild type mice.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that hCETPtg mice have approximately 22% higher cholesterol content in their brains compared to wild-type mice brains ( Oestereich et al, 2022 ). The elevated cholesterol content in the brain and the periphery of hCETPtg mice could differentially affect the distribution and elimination kinetics of the very lipophilic CETP inhibitors (evacetrapib has an octanol to water partition coefficient of logP 7.56) ( Small et al, 2015 ). Due to these fundamental physiological differences, the pharmacokinetic parameters of a CETP inhibitor should be assessed in hCETPtg mice rather than wild-type mice.…”
Section: Discussionmentioning
confidence: 99%